Synthesizing Submicron Particles for Li-ion Batteries: Spray-Drying & Electrostatic Precipitation - Hálová, Hana; Chladil, Ladislav; Preisler, Lukáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
The paper explores innovative methods for producing submicron particles for Li-ion batteries, focusing on spray-drying and electrostatic precipitation. Spray-drying synthesis faces challenges in generating sufficient quantities of product. To address this and also due to the high initial cost, an apparatus integrating an ultrasonic atomizer, drying chamber and modified electrostatic precipitator was designed. This setup enables precise control of parameters, ensuring the production of homogeneous, small-sized particles.
Keywords: spray-drying synthesis; electrostatic precipitation; Li-ion; cathode material; electrostatic precipitator design